Prospects of using the artificial intelligence technologies in jurisprudence and law enforcement - Muravska, Yuliia; Metelskyi, Ihor; Romaniv, Ruslan (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
This article examines the main advantages of artificial intelligence technologies using in jurisprudence and law enforcement. The purpose of this article is an attempt to formulate the prospects for the use of artificial intelligence technologies in jurisprudence and law enforcement. The authors identify the threats and formulate the prospects for the use of AI in jurisprudence and law enforcement. The relevance of this research is, accordingly, explained by the need to conduct a comparative organizational and legal analysis of the liability of manufacturers/developers of software based on AI technologies and lawyers and law enforcement officers in case of an error or wrong decision in the process of using AI in their professional activities. As a result of the study, the authors reviewed the services that optimize access to and analysis of legislation and judicial practice, noted the results of the assessment of the global market for artificial intelligence software, formulated a number of advantages of using artificial intelligence technologies in jurisprudence and law enforcement, identified the main areas of diversification of the areas of application of AI technologies that are related to the ones under study, proposed solutions in the situation of inconsistency of AI forecasts, and formulated a The article emphasizes the need to adopt changes and improve the qualifications of employees in the field of law and law enforcement. The authors come to the conclusion that the use of artificial intelligence in legal and law enforcement practice opens up new opportunities, but may also be subject to relevant threats. Therefore, when using AI technologies, lawyers, for example, should adhere to the principles of data privacy and security, and law enforcement officers will need to introduce new training to be able to successfully adapt to this new environment.